Transport Network Resilience: Present and Future Challenges - Chalkiadakis, Charis; Vlahogianni, Eleni (Technical Annals, 2025)
Departing from its classical definition, resilience has been deemed as a key element for the transportation network management as a proxy of the behavior of transportation networks under both disastrous events and non-recurrent system’s conditions. In the present paper we provide a detailed taxonomy of resilience quantification and applications to modern transportation systems. The definitions of resilience found in literature are summarized, as well as methods, metrics, and models used in various studies are critically assessed. Moreover, we delve into the state-of-the art methods for the quantification of resilience. The analyses reveal specific challenges springing from the technological and communication advancements in the transportation sector that are critically discussed and future directions for integrating the concept of resilience in the context of smart cities via smart vehicles and infrastructures are identified.